Development of a health literacy scale for preconception care: a study of the reproductive age population in Japan - Maiko Suto; Haruhiko Mitsunaga; Yuka Honda; Eri Maeda; Erika Ota; Naoko Arata (BMC, 2021)
Abstract Background Preconception care aims to improve both maternal and child health in the short as well as long term, along with providing health benefits to adolescents, women, and men, whether or not they plan to become parents. However, there is limited evidence regarding the effectiveness of interventions for improving preconception health in population-based settings. To accumulate evidence in this field, this study focused on the concept of health literacy, and aimed to develop a self-report health literacy scale in Japanese, focusing on preconception care. Methods We conducted a cross-sectional online survey. Participants were recruited from December 2019 to February 2020 from the registered members of a web-based research company. Participants were Japanese men and women aged 16-49 (n = 2000). A factor analysis was conducted to select both factors and items for health-related behavior and skills (33 initial items were generated), along with an item response theory analysis to examine how the 16 items were related to people's knowledge of preconception care. Results We developed a 6-factor (including "appropriate medical examinations," "appropriate diet," "stress coping," "healthy weight," "safe living environment," and "vaccinations"), 25-item behavior and skills scale, as well as a 13-item knowledge scale, to evaluate participants' health literacy around preconception care. A shortened version, consisting of 17 items, was also prepared from the 25 items. The reliability coefficients of total scores and each factor of the behavior and skills scale were comparatively high, with weak-to-moderate correlation between behavior and skills and knowledge. Conclusions The new scale will, ideally, provide information on the current state of preconception care health literacy of the general population. In addition, this scale, which consists of both behavioral/skills and knowledge dimensions, should help support the effective implementation of risk assessment programs and interventions aimed at promoting behavioral changes using a population-based approach. Future studies using different question/administration formats for diverse populations, and considering respondents' opinions on health literacy scales should be effective in improving this scale.